Sistem Pendukung Keputusan Pemilihan Karyawan Terbaik Menggunakan Metode Maut - Bella Maitasari; Ahmad Farisi (SATESI: Jurnal Sains Teknologi dan Sistem Informasi, 2024)
PT XYZ is a company that calculates vessels against buildingsor floating facilities in the oil and gas environment. PT XYZ is engaged in services, located in South Sumatra. PT XYZ has a best employee assessment once a year on a regular basis, but the best employee assessment process is not optimal because the best employee assessment has been carried out based on the highest criteria data collection. This can cause more than one employee assessment, because hrd decides again one of the best employees based on the subjectivity of personal opinion. The results of this study state that the decision support system at PT XYZ has been built using the iteration software developer method and the multi attribute utility theory decision support system method based on black block testing all test cases have been tested and provide results that are as expected and with this application can simplify the process of calculating the best employee assessment and provide objective decisions in a short time.